Propagation of the 2014–2016 Northeast Pacific Marine Heatwave Through the Salish Sea - Khangaonkar, Tarang; Nugraha, Adi; Yun, Su Kyong; Premathilake, Lakshitha; Keister, Julie E.; Bos, Julia (Frontiers in Marine Science, 2021)
Effects and impacts of the Northeast Pacific marine heatwave of 2014–2016 on the inner coastal estuarine waters of the Salish Sea were examined using a combination of monitoring data and an established three-dimensional hydrodynamic and biogeochemical model of the region. The anomalous high temperatures reached the U.S. Pacific Northwest continental shelf toward the end of 2014 and primarily entered the Salish Sea waters through an existing strong estuarine exchange. Elevated temperatures up to + 2.3°C were observed at the monitoring stations throughout 2015 and 2016 relative to 2013 before dissipating in 2017. The hydrodynamic and biogeochemical responses to this circulating high-temperature event were examined using the Salish Sea Model over a 5-year window from 2013 to 2017. Responses of conventional water-quality indicator variables, such as temperature and salinity, nutrients and phytoplankton, zooplankton, dissolved oxygen, and pH, were evaluated relative to a baseline without the marine heatwave forcing. The simulation results relative to 2014 show an increase in biological activity (+14%, and 6% Δ phytoplankton biomass, respectively) during the peak heatwave year 2015 and 2016 propagating toward higher zooplankton biomass (+14%, +18% Δ mesozooplankton biomass). However, sensitivity tests show that this increase was a direct result of higher freshwater and associated nutrient loads accompanied by stronger estuarine exchange with the Pacific Ocean rather than warming due to the heatwave. Strong vertical circulation and mixing provided mitigation with only ≈+0.6°C domain-wide annual average temperature increase within Salish Sea, and served as a physical buffer to keep waters cooler relative to the continental shelf during the marine heatwave.